2014
DOI: 10.4049/jimmunol.1302669
|View full text |Cite
|
Sign up to set email alerts
|

Local Immune Response to Injection of Plasmodium Sporozoites into the Skin

Abstract: Malarial infection is initiated when the sporozoite form of the Plasmodium parasite is inoculated into the skin by a mosquito. Sporozoites invade hepatocytes in the liver and develop into the erythrocyte-infecting form of the parasite, the cause of clinical blood infection. Protection against parasite development in the liver can be induced by injection of live attenuated parasites that do not develop in the liver and thus do not cause blood infection. Radiation-attenuated sporozoites (RAS) and genetically att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 72 publications
1
50
0
Order By: Relevance
“…We recently demonstrated that needle-syringe injection of immunizing doses of P. berghei sporozoites in the mouse skin induces a successive recruitment of polymorphonuclear neutrophils followed by inflammatory monocytes in the skin and dLN 19 . The Protocol Section described above details the procedure used to successfully isolate live myeloid cells from both tissues following multiple injections of large number of sporozoites in the ear dermis (Figures 1 and 2).…”
Section: Representative Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We recently demonstrated that needle-syringe injection of immunizing doses of P. berghei sporozoites in the mouse skin induces a successive recruitment of polymorphonuclear neutrophils followed by inflammatory monocytes in the skin and dLN 19 . The Protocol Section described above details the procedure used to successfully isolate live myeloid cells from both tissues following multiple injections of large number of sporozoites in the ear dermis (Figures 1 and 2).…”
Section: Representative Resultsmentioning
confidence: 99%
“…In our experimental system (C57BL/6 mouse -P. berghei), complete protection was achieved after multiple injections in the ear dermis of highly concentrated suspension of parasites (50,000 RAS in 0.6 µl, 4 injection sites) 19 . In this context, we established the protocol described above to analyze more precisely the local host immune response to immunizing doses of RAS that allowed us to identify 2 major myeloid cell subsets recruited in the skin and dLN in response to the parasite 19 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations